Brazil: smoking and alcoholic beverage consumption in the last ten years (vigitel) and the role of the Dental Surgeon in the prevention of oral cancer (Research, Society and Development, 2021)
The present study aimed to discuss the estimated frequency of smoking and alcohol consumption in the last 30 days, by sex, age group and education level in Brazil in the last ten years, and to analyze the role of the dentist in primary care in relation to the main risk factors for oral cancer. It was carried out through an ecological study with data from VIGITEL between the years 2009 and 2019, which resulted in a positive decrease in the number of smokers, decreasing from 15.5 to 9.8%, and in the number of alcohol consumers especially among young adults, there was an increase from 22.9 to 26.3%. In the analysis of professionals in primary health care, the need for public policies to support oral cancer prevention actions and the updating of dentists in the fight against this pathology was clear. Despite the reduction in the percentage of smokers in Brazil in recent years, the consumption of alcoholic beverages remains unresponsive to government initiatives aimed at combating it. The dental surgeon represents an important actor, within the multiprofessional team, in sensitizing the population to acquire healthy habits and prevent oral cancer.